Utilizing the apical-out enteroids in vitro model to investigate intestinal glucose transport, barrier function, oxidative stress, and inflammatory responses in broiler chickens - Mann, Peter; Liu, Jundi; Yu, Liang-en; Wolfenden, Ross; Li, Yihang (Frontiers in Physiology, 2024)
The conventional 2D intestinal epithelial cell lines have been widely used in investigating intestinal functions, yet with limitations in recapitulating the in vivo gut physiology of chickens. A recently established chicken enteroids model with apical-out nature and the presence of leukocyte components is suggested to represent intestinal mucosal functions. The objectives of this study were to: 1) evaluate basic gut nutrient transport and barrier functions in this model; 2) identify the model effectiveness on studying inflammation and oxidative stress responses. Enteroids were generated from individual villus units that were isolated from small intestine of Cobb 500 broilers embryo. Enteroids viability, morphology, and epithelial cell markers were monitored; barrier function was evaluated by the permeability to fluorescein isothiocyanatedextran (FD4) with or without EDTA and lipopolysaccharide (LPS) challenges; nutrient transport was evaluated by fluorescence-labeled glucose (2NBD-G) with or without transporter blockade; oxidative status was indicated by reactive oxygen species (ROS). The inflammatory and oxidative challenges were induced by LPS and menadione treatment, respectively. Selected marker gene expressions, including tight junction proteins (CLDN-1, CLDN-2, ZO-1, OCCL), epithelial cell markers (Lgr-5, LYZ, MUC-2), cytokines (IL-1β, IL-6, IL-8, IL-10, TNF-α, INF-γ), and antioxidant enzymes (Nrf-2, Catalase, SOD), were determined by RT-qPCR. Data were analyzed by one way ANOVA among treatments. Enteroids cell activity was stable from Approved for External Use d 2 to d 6 and declined at d 7. Epithelial cell marker and cytokine expressions were stable from d 4 to d 6. FD4 permeability was increased after the EDTA treatment (P ≤ 0.05). Transporter mediated 2NBD-G absorption was observed and reduced with glucose transporter blockade (P ≤ 0.05). Enteroids showed classic responses to LPS challenge, including upregulated gene expressions of IL-1β and IL-6, downregulated gene expressions of ZO-1 and OCCL, and increased FD4 permeability (P ≤ 0.05). Enteroids showed increased ROS generation (P ≤ 0.05) in response to oxidative stress. In conclusion, this apical-out enteroids model is a stable alternative in vitro model that exhibits intestinal barrier, nutrient transport, oxidation, and inflammation functions. With this enteroids model, we developed two challenge protocols for evaluating intestinal functions under oxidative stress and inflammation conditions.